Theoretical Predictions of Ge14BixSe76-xIn10 Chalcogenide Glasses - Gupta, Shilpa; Saxena, Manish (IJRDO-Journal of Applied Science, 2016)
Chalcogenide glasses have attractedmuch attention in recent past as physicalproperties of chalcogenide glasses make themideal for incorporation into lasers and other activedevices. In the present work, the effect on thephysical properties of Ge14BixSe76-xIn10 (x = 2, 4,6, 8, 10 at. %) chalcogenide glasses with thevariation in bismuth content has been studiedtheoretically. All the parameters, studied here,have been found to vary linearly with change in Biconcentration which indicates this system suitablefor phase change optical recording and findapplications in rewritable optical recording.